Exact Outage Performance Analysis of Amplify-and-forward-aware Cooperative NOMA - Dinh-Thuan Do; Tu-Trinh T. Nguyen (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2018)
In this paper, new radio access scheme that combines Amplify-and-Forward (AF) relaying protocol and non-orthogonal multiple access (NOMA) system is introduced. In particular, different scenarios for fixed power allocation scheme is investigated. In addition, the outage probability of both weak and strong user is derived and provided in closed-form expressions. Such outage is investigated in high SNR scenario and comparison performance between these NOMA scenarios is introduced. Numerical simulations are offered to clarify the outage performance of the considered scheme if varying several parameters in the existing schemes to verify the derived formulas.